2012
DOI: 10.1104/pp.112.198713
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Testa16Plays Multiple Roles in Plant Development and Is Involved in Lipid Synthesis and Embryo Development in Canola    

Abstract: Transparent Testa16 (TT16), a transcript regulator belonging to the B sister MADS box proteins, regulates proper endothelial differentiation and proanthocyanidin accumulation in the seed coat. Our understanding of its other physiological roles, however, is limited. In this study, the physiological and developmental roles of TT16 in an important oil crop, canola (Brassica napus), were dissected by a loss-of-function approach. RNA interference (RNAi)-mediated down-regulation of tt16 in canola caused dwarf phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…To further explore the physiological functions of the BnTT16 homologs with regards to seed coat development, we analyzed the seed coat morphology of Bntt16 RNA interference (RNAi) B . napus lines, which were generated using a hairpin RNAi construct and previously confirmed to down‐regulate the expression of all four BnTT16 genes simultaneously (Deng et al ., ; Figures S4 and S5). In B. napus , the inner integument comprises the PA‐accumulating endothelium (ii1) and parenchyma (ii2), while the outer integument is composed of epidermis (oi3), parenchyma (oi2) and palisade (oi1) layers (Nesi et al ., ; Auger et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…To further explore the physiological functions of the BnTT16 homologs with regards to seed coat development, we analyzed the seed coat morphology of Bntt16 RNA interference (RNAi) B . napus lines, which were generated using a hairpin RNAi construct and previously confirmed to down‐regulate the expression of all four BnTT16 genes simultaneously (Deng et al ., ; Figures S4 and S5). In B. napus , the inner integument comprises the PA‐accumulating endothelium (ii1) and parenchyma (ii2), while the outer integument is composed of epidermis (oi3), parenchyma (oi2) and palisade (oi1) layers (Nesi et al ., ; Auger et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, its function in the development of other plant organs has also been reported. While the down‐regulation of this transcription factor in B. napus caused abnormal embryo development and a reduction in silique and seed numbers (Deng et al ., ), a double knock‐out mutant of the MADS‐box genes TT16 and SEEDSTICK in Arabidopsis resulted in a complete lack of endothelium and subsequent defects in the female gametophyte, reduced fertilization, impediments during seed formation and a severely reduced seed set (Mizzotti et al ., ). Since the endothelium plays a fundamental role in the interaction between the maternally derived integuments and the next generation, functioning to protect and nourish the embryo, it seems likely that the reduction or absence of an endothelium may be largely responsible for these phenotypes (Stadler et al ., ; Morley‐Smith et al ., ; Mizzotti et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the mineral nutrients were transferred into seed through seed coat, and were further delivered from endosperm to embryo [36]. It was reported that decreased lipid content accompanied abnormal embryo development in canola rape [37]. In Arabidopsis, the total lipid content of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 18 the kasI seeds was decreased to 33.6% of the WT which led to defective embryo development [38].…”
Section: Lipid Is Essential For Embryo Development and Seed Germinatimentioning
confidence: 99%
“…In Brassica species homologous cloning is used to isolate PA genes by such as DFR / TT3 (Yan et al, 2008; Akhov et al, 2009), ANS/TT18 (Yan et al, 2011), ANR/BAN (Nesi et al, 2009), TT10 (Zhang et al, 2013), TT2 (Wei et al, 2007), TT8 (Padmaja et al, 2014), TT12 (Chai et al, 2009), TT16 (Deng et al, 2012; Chen et al, 2013), TTG1 (Zhang et al, 2009; Yan et al, 2014) and TTG2 (Li et al, 2015). However, homologous cloning has drawbacks.…”
Section: Introductionmentioning
confidence: 99%